(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study discusses the general conditions of education in the town of Mahes in Al-Balqa Governorate starting from the late the Ottoman Era until the beginning of the eighties of the last century, besides the axes of the educational process, which include the Ministry of Education and the duties of employees in the ministry and the directorate of education in Al-Balqa, such as the inspector of education and teachers, as well as town schools that were established before 1981, the educational process and its various stages, and the general conditions of the students in classrooms, shedding light on the names of the teachers and principals of the first generation who took the initiative of preparing the students at that time. Our main source in this study is the many and varied records of grades and results in the schools, which enriched the study with much and varied information, such as the beginning of educational process, the number of the students, the nature and details of the curriculum and its various subjecs that were taught, the grades and levels in each school, some details related to the assessment practiced by faculty members, the levels of students, their social and health conditions, types of education, and the number of students, which we have noticed to have increased in a steady manner over the years. We resorted to some other sources, such as government documents and recent publications.